Multi-wavelength Observations of Mrk 501 during a VHE flare in May 2009 - Pichel, Ana Carolina (2010)
The VHE (E > 100 GeV) blazar Mrk 501 was observed between April 17 and May 5, 2009, as part of a 4.5-months-long multiwavelength campaign from radio to VHE gamma-ray. This source has a history of spectral variability with extreme outbursts. On the night of May 1, Mrk 501 showed a brief period of activity with a high luminosity flare reaching the level of 5 Crabs at VHE gamma-rays with no evidence of correlation with others frequencies. The flare shows a fast variability with an incresed of a factor of 4 in 30 minutes. The source remain in high state for 3 more days. We present here the results for the quiescent and high-state observations with the Whipple 10-m telescope, VERITAS, the Fermi Large Area Telescope, Swift and RXTE observations that were performed within the framework of the organized campaign.